DEVELOPMENT OF THE LOCAL ECONOMY MINIMIZING UNEMPLOYMENT AND IMPROVING THE WELFARE OF THE COMMUNITY AROUND THE SENJA MARKET, SEI BEBANIR KAMPUNG, BERAU REGENCY - Muslimin, Muslimin; Hasnawati, Hasnawati (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The objectives of this study are: 1) to obtain an overview of the condition of the Senja Market in Sei Loadir Bangun Village, Sambaliung District, Berau Regency; 2) to find out the role of local economic development in order to support community economic activities, minimize unemployment/job creation, improve community welfare/income and the sustainability of the socio-economic life of the community in Sei Loadir Bangun Village, Sambaliung District, Berau Regency. The results showed that the Sunset Market in Sei Loadir Bangun Village was an instrument for utilizing the local economy with various types of potential, including agriculture, fisheries, animal husbandry, and small community industries. Utilization of this potential is primarily aimed at improving the welfare and economic growth of villagers through the development of their economic enterprises. The twilight market of Sei Loadir Bangun Village has an important role in the development of the local economy, both related to: community economic activities, minimizing unemployment/job creation, increasing community welfare/income and the sustainability of the socio-economic life of the community in Sei Loadir Bangun Village, Sambaliung District, Berau Regency.